Financial Sector Assessment : Eastern Caribbean Currency Union - World Bank (World Bank, Washington, DC, 2013)
The joint World Bank- International Monetary Fund (IMF) Financial Sector Assessment Program (FSAP) to the countries of the Eastern Caribbean Currency Union (ECCU) was carried out in September and October of 2003. The assessment covered the following: (i) stability issues, including banking system soundness; supervision and regulation of banking; and the adequacy of financial sector crisis management arrangements; and (ii) structural and development issues, specifically competitiveness, efficiency and reach of the financial system including development of non-bank financial institutions and markets. This FSA report summarizes the overall assessment, providing additional detail on the structural and development issues, and highlights the main recommendations that have been provided to the authorities.